A reference framework for process-oriented software development organizations - Fernandes, João M. (2005)
In this paper, a proposal of a generic framework for process-oriented software development organizations is presented. Additionally, the respective way of managing the process model, and the instantiation of their processes with the Rational Unified Process (RUP) disciplines, whenever they are available, or with other kind of processes is suggested. The proposals made here were consolidated with experiences from real projects and we report the main results from one of those projects.